(untitled) (American Journal of Pedagogical and Educational Research, 2026)
The rapid development of modern industry and production processes has led to the widespread use of various technologies, equipment, and chemical substances in enterprises, which poses significant risks to workers’ health and safety. This article analyses the classification, characteristics, and physiological effects of harmful and hazardous occupational factors on the human organism. The study covers physical factors (noise, vibration, radiation, temperature), chemical factors (toxic substances, acids, alkalis), biological factors (microorganisms, bacteria, viruses), and psychophysiological factors (physical overload, nervous tension, monotony). Special attention is given to the phenomena of cumulation, synergism, and combined effects of multiple factors. Modern monitoring technologies, including IoT-based smart safety systems, are examined. The article substantiates that timely identification and assessment of harmful factors, combined with the application of modern protective measures, is the fundamental condition for reducing occupational injuries and diseases, thereby ensuring safe working conditions.